The Influence of Perception, Literacy, and Religiosity on Generation Z's Interest in Islamic Banking - Faqih Ulil Abshor; Astrian Kusumawati; Putri Wulandari; Sela Rachmawati (Jurnal Pendidikan Ekonomi, 2024)
In March 2024, Indonesia's Islamic banking market accounted for just 7% of the country's total banking assets. Given that the majority of Indonesians are Muslims, this scenario demonstrates a discrepancy between the market potential and market share of Islamic banking. The younger generation is one market area with a lot of potential. Generation Z, the millennial generation's offspring, is the youthful generation of today. Critical thinking, creativity, and computer literacy are traits of this generation. This study intends to check how Generation Z's interest in Islamic banking is influenced by perception, literacy, and religion. Quantitative research using a survey approach is the methodology employed. The University of Jember's Generation Z students serve as the research sample, and they were chosen using a rigorous. The study's findings indicate that Generation Z's interest in Islamic banking is significantly influenced by literacy and religiosity. These results highlight how crucial it is to raise Generation Z's awareness of Islamic finance and legislation to pique their interest in Islamic banking. Keywords: generation Z, Islamic banking, perception, literacy, religiosity